From Companies to Markets--Global Developments in Corporate Governance - International Finance Corporation (Washington, DC, 2016)
In May 2015, the IFC Corporate Governance Group called together 40 experts in the field and members of the IFC Corporate Governance Private Sector Advisory Group. These participants explored key changes in international corporate governance standards and codes of best practice in the wake of the recent global financial crisis and how these changes have helped draw corporate attention to sustainability issues. The group found that many issues that became evident regarding banks in the financial crisis, and led to changes in the governance of banks, also have flowed through into broader corporate governance developments. This publication arises from the issues and information from these discussions. Specifically, part A discusses developments from global or regional groups involved in corporate governance. Part B addresses developments in corporate governance practice, and part C looks at developments in corporate governance codes and standards.